Goldbearing deposits of Proterozoic orogenic structures of Ukrainian Shield - HRINCHENKO, O. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
Thіs paper discusses basic manifestations of gold-bearing mineralizations in Proterozoic structures of Ukrainian Shield. Analysis of geological and mineralogical-geochemical properties of gold meneralisation and роssible comparison with orogenic type mineralisation have been carried out. Thіs paper discusses basic manifestations of gold-bearing mineralizations in Proterozoic structures of Ukrainian Shield. Analysis of geological and mineralogical-geochemical properties of gold meneralisation and роssible comparison with orogenic type mineralisation have been carried out.